Determining the sign of the b → sγ amplitude - Gambino, P; Haisch, U; Misiak, M (2005)
The latest Belle and BABAR measurements of the inclusive B̄ → Xsl+l- branching ratio have smaller errors and lower central values than the previous ones. We point out that these results indicate that the sign of the b → sγ amplitude is the same as in the standard model. This underscores the importance of B̄ → X sl+l- in searches for new physics, and may be relevant for neutralino - dark matter analyses within the minimal supersymmetric standard model. © 2005 The American Physical Society.